Near-infrared nonlinearity of a multicomponent tellurium oxide glass at 800 and 1,064 nm - Oliveira, Tamara A.; Manzani, Danilo [UNESP]; Falcao-Filho, Edilson L.; Messaddeq, Younes [UNESP]; Boudebs, Georges; Fedus, Kamil; Araujo, Cid B. de (Springer, 2014)
We report on the nonlinear (NL) optical properties of glassy TeO2-GeO2-K2O-Bi2O3 at lambda = 800 nm and lambda = 1,064 nm. Using the Kerr gate technique with a laser delivering 150 fs pulses at 800 nm, we demonstrated the fast NL response of the samples. The modulus of the NL refractive index, n (2), at 800 nm was similar to 10(-15) cm(2)/W. The Z-scan technique was used to determine n (2) a parts per thousand +10(-15) cm(2)/W, at 1,064 nm with pulses of 17 ps. The two-photon absorption coefficient, alpha (2), was smaller than the minimum that we can measure (< 0.003 cm/GW). The figure of merit n (2)/alpha (2) lambda was calculated and indicates that this glass composition has large potential to be used for all-optical switching.